Umbilical lactate as a measure of acidosis and predictor of neonatal risk: a systematic review. (5th October 2016) - Allanson, ER; Waqar, T; White, CRH; Tunçalp, Ö; Dickinson, JE
Abstract : Background: Umbilical cord lactate is one approach to measuring acidosis and intrapartum hypoxia, knowledge of which may be helpful for clinicians involved in the care of women and newborns. Objective: To synthesise the evidence on accuracy of umbilical cord lactate in measuring acidosis and predicting poor neonatal outcome. Search strategy: Studies published and unpublished between 1990 and 2014 from PubMed/Medline, EMBASE, Cochrane Central Register of Controlled Trials, and clinicaltrials.gov were assessed. Selection criteria: Cross‐sectional and randomised studies that assessed fetal acidosis (using lactate as the index test) with or without an assessment of neonatal outcome. Data collection and analysis: Correlations between index and reference test(s) were recorded, as were the raw data to classify the predictive ability of umbilical lactate for neonatal outcomes. Meta‐analysis of correlation was performed. We plotted estimates of the studies' observed sensitivities and specificities on Forest plots with 95% confidence intervals (CI). Where possible, we combined data using meta‐analysis, applying the hierarchical summary receiver operating characteristics model and a bivariate model. Main results: Twelve studies were included. Umbilical lactate correlated with pH [pooled effect size (ES) −0.650; 95% CI −0.663 to −0.637, P < 0.001], base excess (ES −0.710; 95% CI −0.721 to −0.699, P < 0.001), and Apgar scores at 5 minutes (ES 0.300; 95% 0.193–0.407, P < 0.001). Umbilical lactate had pooled sensitivity and specificity for predicting neonatal neurological outcome including hypoxic ischaemic encephalopathy of 69.7% (95% CI 23.8–94.4%) and 93% (95% CI 86.8–96.3%). Authors' conclusion: Umbilical cord lactate is a clinically applicable, inexpensive and effective way to measure acidosis and is a tool that may be used in the assessment of neonatal outcome. Tweetable abstract: Umbilical cord lactate: a clinically applicable, inexpensive, effective way to measure intrapartum acidosis. Tweetable abstract: Umbilical cord lactate: a clinically applicable, inexpensive, effective way to measure intrapartum acidosis.